The Tangible and Intangible Benefits of Mangrove Forests as a Factor Affecting Community Participation in Mangrove Management - Fathyyah Zulfa Maulidah; Johan Iskandar; Budhi Gunawan (Journal of Tropical Ethnobiology, 2023)
Community participation has been identified as a key factor in ensuring the long-term sustainability and effective governance of these valuable ecosystems. The three pillars of sustainable protected area management are forms of ecological, social and economic management that enhance the function of protected areas and can support human life. Mangrove forests play a crucial role in coastal ecosystems, providing numerous ecological, economic, and socio-cultural benefits to local communities. Understanding the diverse range of tangible and intangible benefits associated with mangrove forests is essential for comprehending the motivations and incentives that encourage community engagement in their conservation and sustainable management. The review highlights the complex interplay between tangible and intangible benefits and their influence on community participation in mangrove management. The review underscores the importance of recognizing and valuing both types of benefits, as they are intertwined and shape the attitudes, behaviors, and decision-making processes of local communities. Interdisciplinary studies that incorporate ecological, economic, social, and cultural dimensions is needed to comprehensively understand the multifaceted benefits of mangrove forests and their role in driving community participation in mangrove management. Such insights can inform policy and management strategies that promote sustainable development and effective conservation of mangrove ecosystems, ultimately contribute to the well-being of both coastal communities and the environment.